Malignancy and survival in dermatitis herpetiformis: a comparison with coeliac disease. Issue 4 (April 1996) - Collin, P; Pukkala, E; Reunala, T
Abstract : BACKGROUND–Dermatitis herpetiformis is a lifelong, gluten sensitive skin disease. Patients with dermatitis herpetiformis, similar to patients with coeliac disease not adhering to a gluten free diet, seem to have increased risk for lymphoma. AIMS–This study looked at the occurrence of malignancy and survival of patients with dermatitis herpetiformis and compared the results with those seen in patients with coeliac disease or in the general population. PATIENTS–A total of 305 adult patients with dermatitis herpetiformis diagnosed at the University Hospital of Tampere in 1970-1992 were studied. Most patients started a gluten free diet and at the end of the study 93% of the patients were adhering to the diet. A control group comprised 383 adult patients with coeliac disease, 81% of them adhered to a gluten free diet, 6% had a normal diet, and in 13% the diet history remained unknown. METHODS–The occurrence of malignant diseases and survival of the patients were assessed up to the end of 1993. Standardised incidence ratios (SIR) with 95% confidence intervals were used for the malignant diseases. The survival of the patients was compared with that of the general population. RESULTS–Thirteen (4.3%) patients with dermatitis herpetiformis developed 14 malignant disorders during the follow up (SIR 1.25; 95% confidence intervals 0.68 to 2.09). A non-Hodgkin's lymphoma occurred in four patients with dermatitis herpetiformis, significantly more than expected (SIR 10.3; 2.8-26.3). Thirteen (4.3%) patients with dermatitis herpetiformis died during the follow up but there was no increased general mortality. In coeliac disease, 13 (3.4%) patients developed malignancy (SIR 1.16; 0.62 to 1.97), 31 (8.1%) patients died but the survival rate did not differ from that in the general population. CONCLUSIONS–The incidence of non-Hodgkin's lymphoma was significantly increased in patients with dermatitis herpetiformis. The results also confirm that the patients with dermatitis herpetiformis treated mainly with a gluten free diet have no increased general mortality.